Differential calcium sensitivity in NaV1.5 mixed syndrome mutants. (20th August 2017) - Abdelsayed, Mena; Baruteau, Alban‐Elouen; Gibbs, Karen; Sanatani, Shubhayan; Krahn, Andrew D.; Probst, Vincent; Ruben, Peter C.
Abstract : Key points: SCN5a mutations may express gain‐of‐function (Long QT Syndrome‐3), loss‐of‐function (Brugada Syndrome 1) or both (mixed syndromes), depending on the mutation and environmental triggers. One such trigger may be an increase in cytosolic calcium, accompanying exercise. Many mixed syndromes mutants, including ∆KPQ, E1784K, 1795insD and Q1909R, are found in calcium‐sensitive regions. Elevated cytosolic calcium attenuates gain‐of‐function properties in ∆KPQ, 1795insD and Q1909R, but not in E1784K. By contrast, elevated cytosolic calcium further exacerbates gain‐of‐function in E1784K by destabilizing slow inactivation. Action potential modelling, using a modified O'Hara Rudy model, suggests that elevated heart rate rescues action potential duration in ∆KPQ, 1795insD and Q1909R, but not in E1784K. Action potential simulations suggest that E1784K carriers have an increased intracellular sodium‐to‐calcium ratio under bradycardia and tachycardia conditions. Elevated cytosolic calcium, which is common during high heart rates, ameliorates or exacerbates the mixed syndrome phenotype depending on the genetic signature. Abstract: Inherited arrhythmias may arise from mutations in the gene for SCN5a, which encodes the cardiac voltage‐gated sodium channel, NaV 1.5. Mutants in NaV 1.5 result in Brugada Syndrome (BrS1), Long‐QT Syndrome (LQT3) or mixed syndromes (an overlap of BrS1/LQT3). Exercise is a potential arrhythmogenic trigger in mixed syndromes. We aimed to determine the effects of elevated cytosolic calcium, which is common during exercise, in mixed syndrome NaV 1.5 mutants. We used whole‐cell patch clamp to assess the biophysical properties of NaV 1.5 wild‐type (WT), ∆KPQ, E1784K, 1795insD and Q1909R mutants in human embryonic kidney 293 cells transiently transfected with the NaV 1.5 α subunit (WT or mutants), β1 subunit and enhanced green fluorescent protein. Voltage‐dependence and kinetics were measured at cytosolic calcium levels of approximately 0, 500 and 2500 nm . In silico, action potential (AP) model simulations were performed using a modified O'Hara Rudy model. Elevated cytosolic calcium attenuates the late sodium current in ∆KPQ, 1795insD and Q1909R, but not in E1784K. Elevated cytosolic calcium restores steady‐state slow inactivation (SSSI) to the WT‐form in Q1909R, but depolarized SSSI in E1784K. Our AP simulations showed a frequency‐dependent reduction of AP duration in ∆KPQ, 1795insD and Q1909R carriers. In E1784K, AP duration is relatively prolonged at both low and high heart rates, resulting in a sodium overload. Cellular perturbations during exercise may affect BrS1/LQT3 patients differently depending on their individual genetic signature. Thus, exercise may be therapeutic or may be an arrhythmogenic trigger in some SCN5a patients. Key points: SCN5a mutations may express gain‐of‐function (Long QT Syndrome‐3), loss‐of‐function (Brugada Syndrome 1) or both (mixed syndromes), depending on the mutation and environmental triggers. One such trigger may be an increase in cytosolic calcium, accompanying exercise. Many mixed syndromes mutants, including ∆KPQ, E1784K, 1795insD and Q1909R, are found in calcium‐sensitive regions. Elevated cytosolic calcium attenuates gain‐of‐function properties in ∆KPQ, 1795insD and Q1909R, but not in E1784K. By contrast, elevated cytosolic calcium further exacerbates gain‐of‐function in E1784K by destabilizing slow inactivation. Action potential modelling, using a modified O'Hara Rudy model, suggests that elevated heart rate rescues action potential duration in ∆KPQ, 1795insD and Q1909R, but not in E1784K. Action potential simulations suggest that E1784K carriers have an increased intracellular sodium‐to‐calcium ratio under bradycardia and tachycardia conditions. Elevated cytosolic calcium, which is common during high heart rates, ameliorates or exacerbates the mixed syndrome phenotype depending on the genetic signature.